CGIAR Research Program on Wheat - Plan of Work and Budget 2020 - CGIAR Research Program on Wheat (CGIAR Research Program on Wheat, 2020)
No further adjustments are planned for 2019-2021, beyond those described in the POWB2019. Although the Heat and Drought Wheat Improvement Consortium (FP2/FP3) was launched in 2019, attracting funders in collaboration with the G20 Wheat Initiative will take longer than anticipated and will continue in 2020. WHEAT needs to attract stronger bilateral funding (Turkey) for winter wheat breeding and pre-breeding. To secure breeding and sustainable intensification successes for the future in Pakistan, WHEAT may have to (re)deploy W1&2 funds to enable continuity through new bilateral funding.